Quantitative determination of free D-Asp, L-Asp and N-methyl-D-aspartate in mouse brain tissues by chiral separation and Multiple Reaction Monitoring tandem mass spectrometry. - Carolina Fontanarosa; Francesca Pane; Nunzio Sepe; Gabriella Pinto; Marco Trifuoggi; Marta Squillace; Francesco Errico; Alessandro Usiello; Piero Pucci; Angela Amoresano (PLoS ONE)
Several studies have suggested that free d-Asp has a crucial role in N-methyl d-Asp receptor-mediated neurotransmission playing very important functions in physiological and pathological processes. This paper describes the development of an analytical procedure for the direct and simultaneous determination of free d-Asp, l-Asp and N-methyl d-Asp in specimens of different mouse brain tissues using chiral LC-MS/MS in Multiple Reaction Monitoring scan mode. After comparing three procedures and different buffers and extraction solvents, a simple preparation procedure was selected the analytes of extraction. The method was validated by analyzing l-Asp, d-Asp and N-methyl d-Asp recovery at different spiked concentrations (50, 100 and 200 pg/μl) yielding satisfactory recoveries (75-110%), and good repeatability. Limits of detection (LOD) resulted to be 0.52 pg/μl for d-Asp, 0.46 pg/μl for l-Asp and 0.54 pg/μl for NMDA, respectively. Limits of quantification (LOQ) were 1.57 pg/μl for d-Asp, 1.41 pg/μl for l-Asp and 1.64 pg/μl for NMDA, respectively. Different concentration levels were used for constructing the calibration curves which showed good linearity. The validated method was then successfully applied to the simultaneous detection of d-Asp, l-Asp and NMDA in mouse brain tissues. The concurrent, sensitive, fast, and reproducible measurement of these metabolites in brain tissues will be useful to correlate the amount of free d-Asp with relevant neurological processes, making the LC-MS/MS MRM method well suited, not only for research work but also for clinical analyses.